Anaerobic Composting of Farmyard Manure as Affected by Chicken Manure, Urea and Waste Water - Sulieman, Hind Mohammed; Elamin, Elamin Abdedlmagid (University of Khartoum Journal of Agricultural Sciences, 2023)
the objectives of this study were to investigate the stage of maturity and to determine nutrient contents of farmyard manure (FYM) composted with 2% chicken manure (CHM), 1% urea, and 25% waste water, during the summer seasons of 1997 and 1998. The treatments were replicated thrice in a completely randomized design. The total number of experimental units was repeated eight times for destructive sampling at 15 days intervals for a period of four months. The treatments were buried in auger holes (90-cm depth) and samples were collected and chemically analysed. The analysis included crude fibre, cellulose, starch, calcium, magnesium, sodium, nitrogen, phosphorus and potassium contents. The stage of maturity of FYM was measured by the biodegradation of crude fibre, cellulose and starch contents which decreased significantly (P≤ 0.005). The rate of crude fibre decomposition was highest in urea followed by CHM and waste water. The rate of cellulose decomposition of both urea and waste water treatments was significantly higher than the CHM and control treatments. Starch disappeared in the 12th week in CHM treatment and in the 14th week in waste water treatment. CHM treatment was superior in calcium release followed by waste water and urea treatments. The lowest sodium was detected in waste water treatment followed by both CHM and urea. Waste water, however, showed the highest nitrogen and phosphorus contents compared to the other treatments. Potassium content was the highest in CHM followed by urea and waste water. In conclusion, the best compost ripening time was after three months when its nutritive value was the highest and the physical properties were best